Hubungan Antara Jumlah Hafalan Al-Qur’an dengan Mahārah Qirā’ah Siswa Kelas XI SMK It Ibnul Qayyim Makassar: - - Nurhalisa Nurhalisa; Susiawati Susiawati; Hasmawati Hasmawati (FKIP, Universitas Palangka Raya, 2026)
This article discusses the relationship between the amount of Qur'an memorization and Arabic reading skills among students in Islamic educational institutions. Arabic language learning is closely related to activities of reading and understanding the Qur'an, and memorizing the Qur'an not only aims to preserve the authenticity of the revelation but also has the potential to support the mastery of Arabic, particularly in reading skills. Through the memorization process, students become familiar with vocabulary, sentence structures, and correct Arabic pronunciation, which can help improve their Arabic reading ability. This study employs a quantitative approach with a correlational research design. The research data were obtained from 26 eleventh-grade students who were selected as the sample using a total sampling technique. Data collection was conducted through documentation to obtain data on the students’ Qur'an memorization and through tests to measure their Arabic reading skills. The data were then analyzed using the Spearman Rank correlation test with a significance level of 5%. The results show that the correlation coefficient value of 0.811 is greater than the rtable value of 0.388, indicating a strong and positive relationship between the amount of Qur'an memorization and the students’ Arabic reading skills. These findings indicate that the more Qur'an memorization students possess, the better their Arabic reading skills tend to be. Therefore, the Qur'an memorization (tahfiz) program can serve as a supporting factor in improving Arabic reading skills and should continue to be developed and integrated with Arabic language learning in Islamic educational institutions.